Thrombocytopenia in pregnancy in a tertiary care hospital: a retrospective study - Varghese, Shiny; Kour, Gagandeep; Dhar, Tapasya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To investigate the etiology, obstetrical risk factors, complications and outcomes of pregnancies affected by thrombocytopenia. Methods: A retrospective surveillance study was conducted on the basis of hospital records of 1532 women who delivered during a period of one year, in Christian Medical College and Hospital, Ludhiana, India. Clinical data including basic history, physical examination and investigations of those women who had thrombocytopenia, was evaluated and compiled into three groups depending upon the etiological factors. Results: Sixty four of 1532 women (4.2%) had thrombocytopenia of varying severity. 77.8% of these women had gestational thrombocytopenia (GT) as the commonest cause. Pregnancy specific hypertension and HELLP syndrome (hemolysis, elevated liver enzymes, and low platelets) accounted for 20.6% cases whereas in 3.2% of pregnant women, idiopathic thrombocytopenic purpura (ITP) was the causative factor. A higher rate of IUGR (Intrauterine growth restriction), placental abruption and labor induction was noted among those gravidas who had moderate to severe thrombocytopenia. Maternal mortality, bleeding complications and adverse perinatal outcomes were not seen in this study. Conclusions: Commonest cause of thrombocytopenia in pregnancy is GT, followed by preeclampsia, eclampsia and HELLP syndrome. ITP is a rare cause of this disorder in pregnancy. Early detection and treatment of expected complications is the key focus in management of such cases.